The history of the Irish famine
1 online resource (4 volumes)
Keywords: "The Great Irish Famine remains one of the most lethal famines in modern world history and a watershed moment in the development of modern Ireland that is controversial to this day. In the space of only four years, Ireland lost twenty-five percent of its population as a consequence of starvation, disease and large-scale emigration. The narratives of those who perished, those who survived and those who emigrated form an integral part of this history and these volumes will make available, for the first time, some of the original documentation. Comprehensive editorial apparatus accompany the original texts along with appendices that point the way for further study"--